IMPLEMENTATION OF NORMALIZED PID CONTROLLER FOR SYSTEMS WITH VARYING DELAY - BOLHASSAN, NURUL SHAFINAZ (Universiti Teknologi PETRONAS, 2016)
In a networked control system where sensor and actuator signals are transmitted over a communication network, delays are introduced into the system. Such delays affect the stability and performance of a closed loop control system. The proposed PID controller needs to be designed and tuned so that it can compensate the effect of delays not only from the communication networks, but also those inherent in the process.